2018
DOI: 10.1097/md.0000000000012151
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for postoperative pancreatic fistula

Abstract: This study was designed to analyze the risk factors for postoperative pancreatic fistula (POPF) after pancreaticoduodenectomy (PD).Between September 2015 and August 2017, 170 successive patients underwent a radical PD in the Department of Pancreatic Surgery, Union Hospital, Wuhan. We carried out a retrospective study of these cases and the prospective conditions, which might be related to POPF, were examined with univariate and multivariate analysis. POPF was defined as a drain output of any measurable volume … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 52 publications
0
22
0
Order By: Relevance
“…A total of 37 studies 10,11,[28][29][30]33,34,37,39,44,45,[48][49][50][51][52][53]55,[58][59][60][61][62][63][64]72,74,75,77,81,83,87,87,[123][124][125] with 14,471 patients investigated MPD diameter as a risk factor for CR-POPF, applying different cut-offs. Irrespective of the cut-off, duct diameter was associated with CR-POPF (OR 3.14, 95% CI 2.53-3.90, P < 0.01) (Fig.…”
Section: Association Of Mpd Size and Popfmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 37 studies 10,11,[28][29][30]33,34,37,39,44,45,[48][49][50][51][52][53]55,[58][59][60][61][62][63][64]72,74,75,77,81,83,87,87,[123][124][125] with 14,471 patients investigated MPD diameter as a risk factor for CR-POPF, applying different cut-offs. Irrespective of the cut-off, duct diameter was associated with CR-POPF (OR 3.14, 95% CI 2.53-3.90, P < 0.01) (Fig.…”
Section: Association Of Mpd Size and Popfmentioning
confidence: 99%
“…Twelve studies 10,44,55,59,63,72,75,77,81,83,123,124 including 4660 patients classified MPD diameter of r 3mm as a high risk for CR-POPF development (OR 2.99, 95% CI 2.17-4.13, P < 0.01). Another 20 studies 11,29,30,33,37,39,44,45,[48][49][50][51]58,61,62,64,74,79,87,125 with 9067 patients used MPD diameter of ≤3 mm as the high-risk cut-off, although the results were comparable (OR 3.66, 95% CI 2.62-5.12, P < 0.01).…”
Section: Association Of Mpd Size and Popfmentioning
confidence: 99%
“…One of the most important factors of morbidity and mortality following PD is the incidence of POPF. Many previous studies have reported several risk factors in PD, such as gender (male)[19], BMI > 25 kg/m 2[20] , anastomotic method[6,21], external stent[22], fasting blood glucose level < 108.0 mg/dL[23], etc . However, the most reliable consensus risk factors for POPF after PD are small pancreatic duct (≤ 3 mm) and soft pancreas[6,21,23-28], which reflect the possibility that adequate anastomosis of the pancreatic duct and active exocrine function are deeply involved in the development of POPF.…”
Section: Pancreaticoduodenectomymentioning
confidence: 99%
“…The modern incidence of clinically significant pancreatic fistulae as defined by the International Study Group of Pancreatic Surgery is variable and dependent on numerous factors and patient characteristics. Rates in the literature range from 5% to greater than 30% [13][14][15][16][17]. Utilizing organ-space surgical infection as a surrogate may underestimate the true incidence of pancreatic fistula but is nonetheless a useful metric to consider.…”
Section: Discussionmentioning
confidence: 99%